KERUING and APITONG: A Timely Review of the Perfect ChoiceWood Species for Crossarms and Brace Arms, including Data on Copper Naphthenate Treatments - Wong, Andrew H.H.; Freeman, Michael H. (IRGWP, 2012)
Apitong or the wood species more commonly known as Keruing is an important tropical hardwood known for its high strength to weight ratio and its reasonable durability and preservative treatability. This wood has been exported from managed permanent forest estates in Malaysia into the United States for over 4 decades for its widespread use in wooden utility industry brace arms and crossarms, yet currently it is not listed as an approved species by either ANSI or ASTM. Because it has not had any significant failures in its use patterns now for almost four decades, members of the AWPA Utility Users Task Group have asked for a comprehensive and Critical review of the species and its durability or treatability properties, since they have been using it and specifying it in their systems under product acception for years. This paper is meant to be a comprehensive review of both public domain data and privately sponsored studies to yield additional product information, for those using, specifying and treating this tropical, sustainable species from Malaysia.